Pengaruh Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) Terhadap Hasil Belajar Siswa Pada Sub Tema 3 Pekerjaan Orang Tuaku Kelas IV Di UPTD SD Negeri 122345 Pematang Siantar - Kristina Siregar; Theresia Monika Siahaan; Minar Trisnawati Tobing (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the influence to see how much the cooperative learning model the student team achievement division (stad) has affected the results of student studies on the third grade iv sub theme of my parents' work at uptd SDN 122345 shuttle dikes. There are 2 hypotheses in this study: (ha) there was a cohesive learning model of stad that affected students' learning on sub theme 3 of my parents' work iv uptd elementary and 122345 siantar. (h0) there is no influence of a cooperative learning model typical of stad in students' study on sub theme 3 of my parents' work iv uptd elementary n 122345 siantar. The study was carried out in the year 2023/2024 in October. This method of research is an experiment with a type of pre-prototype design design a one-group prepackaged design design. The sample of this study is 20 students made up of 7 boys and 13 girls. The data-collection technique used was testing and documenting. Data are processed using a t-test analysis technique based on the results of the hypotheses obtained by the study of the class iv student based on the test results of the test results normal.05 that the significance of 0,000 0.05 and can conclude that there was influence in the use of student team team achievement devision (stad) cooperative learning models on the theme 4 different kinds of subtheme 3 work of my parents in UPTD SDN 122345 Pematang Siantar.